2013
DOI: 10.1159/000350111
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Autophagy by Simvastatin through Inhibition of Rac1-mTOR Signaling Pathway in Coronary Arterial Myocytes

Abstract: Background/Aims: In addition to their action of lowering blood cholesterol levels, statins modulate biological characteristics and functions of arterial myocytes such as viability, proliferation, apoptosis, survival and contraction. The present study tested whether simvastatin, as a prototype statin, enhances autophagy in coronary arterial myocytes (CAMs) to thereby exert their beneficial effects in atherosclerosis. Methods and Results: Using flow cytometry, we demonstrated that simvastatin significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 46 publications
11
101
0
Order By: Relevance
“…It was demonstrated that statins improve bacterial clearance by the host and improve the efficacy of TB drugs by promoting autophagy through inhibition of the HMG-CoA reductase pathway (Parihar et al, 2014). Furthermore, there are some reports claiming that statins also enhance autophagy in an mTOR-dependent way by inhibiting the RAC1-mTOR signaling pathway (Wei et al, 2013). The full mechanisms behind the autophagy-inducing effects of statins are still not fully elucidated; however, the effects observed from statin administration are promising and may provide another possible complement to TB therapy.…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…It was demonstrated that statins improve bacterial clearance by the host and improve the efficacy of TB drugs by promoting autophagy through inhibition of the HMG-CoA reductase pathway (Parihar et al, 2014). Furthermore, there are some reports claiming that statins also enhance autophagy in an mTOR-dependent way by inhibiting the RAC1-mTOR signaling pathway (Wei et al, 2013). The full mechanisms behind the autophagy-inducing effects of statins are still not fully elucidated; however, the effects observed from statin administration are promising and may provide another possible complement to TB therapy.…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…Simvastatin was previously shown to enhance autophagy in osteoblastic cells and coronary arterial myocytes (14,17). The present study determined whether simvastatin elevated ox-LDL-induced autophagy in macrophages.…”
Section: Simvastatin Enhances Ox-ldl-induced Macrophage Autophagymentioning
confidence: 81%
“…Simvastatin is a widely used statin, that exhibits lipid and non-lipid effects (12,13). Recently, simvastatin was shown to enhance autophagy in coronary arterial myocytes, through inhibition of the Rac1-mammalian target of rapamycin (mTOR) signaling pathway (14). However, the effects of simvastatin on macrophage autophagy remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblotting was performed as previously described (2,(29)(30)(31)(32)(33)(34). Briefly, ovaries from different experimental groups were sonicated in lysis buffer containing a protease inhibitor cocktail (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%